The Shape of the New : Four Big Ideas and How They Made the Modern World - Montgomery, Scott L.; Chirot, Daniel (Book collections on Project MUSE., 2015)
Authors Montgomery and Chirot make the case that to read the works of the great thinkers is to gain insight into the ideas shape how we think and what we believe. They provide portraits of heirs of the Enlightenment that embodied its highest ideals about progress: Adam Smith, Thomas Jefferson, Alexander Hamilton, Charles Darwin, and Karl Marx. Over time and in the hands of their followers and opponents, their thoughts transformed the nature of our beliefs, institutions, economies, and politics. Contradictions in these ideas have been used in the service of brutal systems such as slavery and colonialism; appropriated and twisted by monsters like Stalin and Hitler, and provoked reactions against the Enlightenment's legacy by Islamic Salafists and the Christian Religious Right. Montgomery and Chirot argue that in order to understand the ideological and political conflicts of today, we must familiarize ourselves with the history and internal tensions of these world-changing ideas. With passion and conviction, they compel us to recognize their central importance as historical forces and pillars of the Western humanistic tradition--From page 2 of cover.